2008
DOI: 10.1002/pssb.200879858
|View full text |Cite
|
Sign up to set email alerts
|

Excitons in a perfect quasi‐1D organic quantum wire, an isolated polydiacetylene chain

Abstract: Symposium on Modern Developmnets in Multiphysics Materials Simulations, Berlin, GERMANY, 2008International audienceThe exciton in single luminescent polydiacetylene (PDA) chains dispersed in their single crystal monomer matrix is studied. As reported these quantum wires have the properties of a perfect quasi-1D semiconducting system. The macroscopic spatial coherence of a single exciton state on a chain as a function of temperature is investigated using an interference experiment. The interference pattern cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 13 publications
(14 reference statements)
1
13
0
Order By: Relevance
“…represented by ladder-type ( p -phenylene), LPP, in which the backbone is forced into a rigid, ordered structure by synthesis. The prototypical example for an ordered system is a defect-free single polydiacetylene (PDA) chain embedded in its own monomer crystal as extensively investigated by Schott et al The common motif in the PL spectra of P3HT, LPP, and PDA is that the ZPLs are the most intense transitions, with the relative ZPL intensity showing an increasing trend in the order P3HT, LPP, PDA. Within the framework of the J-aggregate theory by Spano et al, this trend implies an increase in the coherence length in the same order.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…represented by ladder-type ( p -phenylene), LPP, in which the backbone is forced into a rigid, ordered structure by synthesis. The prototypical example for an ordered system is a defect-free single polydiacetylene (PDA) chain embedded in its own monomer crystal as extensively investigated by Schott et al The common motif in the PL spectra of P3HT, LPP, and PDA is that the ZPLs are the most intense transitions, with the relative ZPL intensity showing an increasing trend in the order P3HT, LPP, PDA. Within the framework of the J-aggregate theory by Spano et al, this trend implies an increase in the coherence length in the same order.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Those conditions might include alignment of chains and minimization of structural relaxations, possibly by self-assembly in block polymers. [41][42][43] These conditions could also promote coherence, like that reported previously, [34][35][36] which might further improve transport. We conclude that at least in this case, conjugated molecular chains give fast transport; they are wires for excitons.…”
mentioning
confidence: 80%
“…5 The spectroscopy of isolated chains of these PDA in their single crystal monomer matrix has been studied, and it has been showed that they behave as perfect quasi-1D systems 6 on which the exciton is spatially coherent over the whole chain length at low temperature (micrometers), being an electronic state of the whole chain. 7,8 Another property of interest of some PDA is that several electronic structures exist for these conjugated polymer chains, evidenced by different colors of the solid polymer, the most frequent being "blue " and " red ", the latter but not the former being luminescent, with high quantum yields at low temperature. 9À11 The origin of these differences, and the corresponding structural differences which must exist, are still a matter of debate, 12 and one of us has recently provided computational evidence for a model where blue chains are planar and red ones are twisted (nonplanar).…”
Section: ' Introductionmentioning
confidence: 99%